Between Muslim and Jew : the problem of symbiosis under early Islam - Wasserstrom, Steven M. (Princeton, New Jersey : Princeton University Press, 1995)
Steven Wasserstrom undertakes a detailed analysis of the "creative symbiosis" that existed between Jewish and Muslim religious thought in the eighth through tenth centuries. Wasserstrom brings the disciplinary approaches of religious studies to bear on questions that have been examined previously by historians and by specialists in Judaism and Islam. His thematic approach provides an example of how difficult questions of influence might be opened up for broader examination. In Part I, "Trajectories," the author explores early Jewish-Muslim interactions, studying such areas as messianism, professions, authority, and class structure and showing how they were reshaped during the first centuries of Islam. Part II, "Constructions," looks at influences of Judaism on the development of the emerging Shi'ite community. This is tied to the wider issue of how early Muslims conceptualized "the Jew." In Part III, "Intimacies," the author tackles the complex "esoteric symbiosis" between Muslim and Jewish theologies. An investigation of the milieu in which Jews and Muslims interacted sheds new light on their shared religious imaginings. Throughout, Wasserstrom expands on the work of social and political historians to include symbolic and conceptual aspects of interreligious symbiosis. This book will interest scholars of Judaism and Islam, as well as those who are attracted by the larger issues exposed by its methodology. Originally published in 1995. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- CONTENTS -- PREFACE -- INTRODUCTION -- CHAPTER ONE. Who Were the Jews? Problems in Profiling the Jewish Community under Early Islam -- CHAPTER TWO. The Jewish Messiahs of Early Islam -- CHAPTER THREE. Shi'ite and Jew between History and Myth -- CHAPTER FOUR. Jewish Studies and Comparative Religion in die Islamicate Renaissance -- CHAPTER FIVE. Origins and Angels: Popular and Esoteric Literature in Jewish-Muslim Symbiosis -- CHAPTER SIX. Conclusion: Reflections on the History and Philosophy of Symbiosis -- BIBLIOGRAPHY -- INDEX.
Includes bibliographical references (pages 239-278) and index.
Print version record.
Master record variable field(s) change: 650
Keywords: Islam -- Relations -- Judaism; Judaism -- Relations -- Islam; Jews -- Islamic Empire -- Intellectual life; Judaism -- Islamic Empire -- History; HISTORY -- Middle East -- General; RELIGION -- Judaism -- General; Interfaith relations; Islam; Jews -- Intellectual life; Judaism; Islamic Empire; Electronic books; History